SMEs and European integration : internationalisation strategies - Hegge, Birgit, 1968- (London ; New York : Routledge, 2002)
This book is about integration, internationlaisation and location of Small and Medium-sized Enterprises (SMEs)
Includes bibliographical references (p. [208]-216) and index.
osa 20/05/14
Loans
Keywords: Europe -- Economic integration; Small business -- Europe -- Finance -- Case studies; Economic and Monetary Union; Euro; Currency question; Medical instruments and apparatus industry -- France; Medical instruments and apparatus industry -- Germany